Síntese, caracterização e aplicação de um polímero molecularmente impresso (MIP) com atividade catalítica para oxidação de epinefrina - Sartori, Lucas Rossi (2010)
The technique for preparation of molecularly imprinted polymers (MIP), since its first description in 1972, has promoted relevant advances to different segments of Analytical Chemistry, particularly in procedures for solid phase extraction. However, the use of imprinted polymers with catalytic activity is still young. In the present work was synthesized a MIP (MIP-MAA) with selective catalytic activity for the oxidation of epinephrine (EP) by hydrogen peroxide (H2O2) using hemin and methacrylic acid (MAA) as functional monomers in the synthesis of the polymer, giving to the MIP selective and prosthetic binding sites for the template molecule of EP and also increasing the activity of the material in water. Simultaneously were prepared the following materials: non-imprinted polymer (NIP1), non-imprinted polymer without hemin (NIP2) and imprinted polymer with hemin and 4-vinylpyridine (MIP-4VPy). The materials were synthesized using the technique of bulk by free radical polymerization thermo-activated, as described by Santos et al (2007) with minor modifications. After synthesis, the materials were milled, dried and sieved to a maximum diameter of 106 µm. Afterward, the template molecule was extracted from MIP with a solution of methanol: acetic acid (4:1) (v / v) and the final product was submitted to analysis of physical characterization, such as scanning electron microscopy (SEM), thermogravimetry (TG) and infrared (IR). The detection technique was amperometry with the potential fixed in 0.0 V vs. Ag / AgCl, which was coupled to the output of a system of flow injection analysis (FIA) in a single line mode. The FIA system consisted of the introduction of the sample EP (tris-HCl 0.1 mmol L-¹, pH 8.0, 120 µL) in a carrier stream of H2O2 (300 µmol L-¹, 0.9 mL min-¹). After percolation of the sample on the biomimetic reactor, the catalysis of the EP oxidation by H2O2 occur, being the product formed monitored by amperometry through the variation of current versus time. The MIP-MAA showed higher catalytic activity of NIP1, NIP2 and MIP-4VPy, demonstrating the effectiveness of molecular imprinting. The level of interference observed for molecules similar to the EP was less than 45% considering the signal amplitude. Through physical characterization was possible to detect the presence of morphological differences between the MIP-MAA, NIP1 and NIP2, especially in the TG analysis.